Bowel Dysfunction Related to Spina Bifida: Keep It Simple. Issue 11 (November 2017) - Brochard, Charlène; Peyronnet, Benoît; Dariel, Anne; Ménard, Hélène; Manunta, Andréa; Ropert, Alain; Neunlist, Michel; Bouguen, Guillaume; Siproudhis, Laurent
Abstract : BACKGROUND: Although care of urological disorders in spina bifida is well established, there is yet no agreement on a standardized approach to bowel dysfunction in this population. OBJECTIVE: The purpose of this study was to assess bowel dysfunction using validated instruments and the risk factors in adults with spina bifida. DESIGN: A multidisciplinary team prospectively collected patient data, focusing on anorectal and urological symptoms. SETTINGS: The study was conducted with data from a French referral center for spina bifida. PATIENTS: A total of 228 adults with spina bifida (sex ratio men:women, 92 (40%):136 (60%)) with a median age of 34.7 years (range, 26.8–44.7 y) were assessed. MAIN OUTCOMES MEASURES: Factors associated with severe fecal incontinence (Cleveland Clinic Incontinence Score ≥9) and severe bowel dysfunction (Neurogenic Bowel Dysfunction score ≥14) were assessed in a multivariate analysis model. RESULTS: The prevalence rates of severe fecal incontinence and severe bowel dysfunction were 60% (130/217) and 42% (71/168). Bowel dysfunction was the second most common major concern of patients after lower urinary tract dysfunction. Male sex, obesity, urinary incontinence, and a Knowles–Eccersley–Scott symptom constipation score ≥10 were independently associated with severe fecal incontinence. Patients with soft stools had significantly less severe bowel dysfunction. Neither neurologic level nor other neurologic features of spina bifida were associated with severe fecal incontinence or severe bowel dysfunction. LIMITATIONS: The recruitment of patients with spina bifida through a national referral center might have resulted in selection bias, and some data were missing especially regarding BMI and Neurogenic Bowel Dysfunction score (21% and 26% of missing data). CONCLUSIONS: The prevalence rates of severe fecal incontinence and severe bowel dysfunction in adults with spina bifida were high and were adequately perceived by the patients. The present study emphasized the association of bowel dysfunction and fecal incontinence with obesity, urologic disorders, and stool consistency rather than neurologic features. SeeVideo Abstract athttp://links.lww.com/DCR/A394 . Abstract : Supplemental Digital Content is available in the text.